The Action of Immobilized Thrombin on Factor VIII, Fibrinogen and a Synthetic Tripeptide - Brown, J E; Carton, C L; Dietz, A S; Baugh, R F; Hougie, C (Thrombosis and Haemostasis, 1978)
Bovine thrombin was insolubilized by attachment to cyanogen bromide-activated Sepharose (Sepharose-thrombin) or to activated (Affi-Gel 10) agarose containing a 10 Å long arm (Affi-Gel-thrombin). Coupling in both instances approximated 7,000 units of thrombin per ml packed gel as determined by 125I-thrombin incorporation. The thrombin beads hydrolyzed the synthetic tripeptide Bz-Phe-Val-Arg-pNA (S-2160) at different rates, with the Sepharose-thrombin more active (220 esterase units per ml) than Affi-Gel thrombin (20.4 units per ml). The Km was significantly higher for the insolubilized thrombins (2×10-3M) than uncoupled thrombin (Km = 8×10-5M). The Sepharose- thrombin activated factor VIII significantly more rapidly than Affi-Gel-thrombin. Neither matrix-bound thrombin clotted a fibrinogen solution or liberated significant amounts of fibrinopeptides over 48 hr. This data indicates that a proteolysis of factor VIII, rather than a complex with thrombin, is the method of activation of factor VIII and that factor VIII is more accessible to the action of immobilized thrombin than is fibrinogen.